Pemeriksaan Penunjang Mikrobiologi untuk Diagnosis Infeksi Mycobacterium Other Than Tuberculosis (MOTT) - Devita, Arleen; Dharmawan, Ade (Jurnal Biomedika dan Kesehatan, 2024)
Mycobacterium other than tuberculosis (MOTT) is an environmental bacterium that can be an opportunistic pathogen. These bacteria are resistant to various types of disinfectants and antibiotics because they have the characteristics of thick cell wall peptidoglycan that are rich in lipids and mycolic acid. There are now over a hundred MOTT species, some of which are known to infect people with immune system disorders such as chronic obstructive pulmonary disease (COPD), cystic fibrosis (CF), people with a history of tuberculosis (TB), HIV infection, or diabetes mellitus, but can also infect individuals with good immune systems. This type of mycobacterium can also cause nosocomial infections because it can contaminate hospital water as well as medical devices such as bronchoscopes, endoscopes, and dialysis fluids. Infections in humans originate from environmental exposure and spread through ingestion or inhalation. The clinical manifestations of MOTT infection can be pulmonary and extrapulmonary infections, including skin, soft tissue, the gastrointestinal system, bones, and joints, and disseminated with symptoms that are difficult to distinguish from a Mycobacterium tuberculosis infection. Therefore, it is necessary to conduct supporting examinations, in particular microbiological examinations, to detect and identify the species of MOTT and then determine the appropriate therapeutic management. The types of microbiological examination that can be performed are microscopic examination with acid-fast staining, culture, identification with biochemical tests, molecular tests, and immunodiagnostic tests.